(untitled) (International journal of medical sciences, 2026)
Systemic lupus erythematosus (SLE) is a chronic, autoimmune, multisystem inflammatory disease characterized by the production of autoantibodies and immune complex deposition, leading to tissue damage across multiple organ systems. The disease predominantly affects women of reproductive age and demonstrates a highly heterogeneous clinical presentation ranging from mild mucocutaneous manifestations to life-threatening renal, neurological, and hematological involvement. The pathogenesis of SLE involves genetic susceptibility, environmental triggers, hormonal influences, and immune dysregulation, particularly involving B cells, T cells, and type I interferon pathways. Advances in immunopathogenesis have led to the development of targeted immunosuppressive therapies, including biologic agents aimed at B-cell modulation and cytokine inhibition. This article reviews the mechanisms of multisystem involvement, diagnostic principles, and contemporary immunosuppressive treatment strategies for SLE, highlighting recent therapeutic innovations and challenges in long-term disease management.